2018
DOI: 10.1108/aaaj-07-2017-3005
|View full text |Cite
|
Sign up to set email alerts
|

Sites of translation in digital reporting

Abstract: Purpose The purpose of this paper is to analyse the process by which “analogue” corporate reports produced under a “paper paradigm” are translated into a machine language as required by digital reporting. The paper uses Austin and Searle’s linguistic speech act theory to examine how digitally translating reporting information into atomised data affects the infrastructure and practice of accounting. Design/methodology/approach Extensive interview and observation evidence focussed on the IFRS Foundation’s digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…The contributions to this AAAJ special issue also demonstrated that there is much still to be done for us as a community to begin to comprehend and address the impact of language and translation on our innovative and (hopefully) more inclusive knowledge creation endeavors. Thus, there is a considerable scope for the exploration of the power implications of language skills, and of the use of ELF, in diverse settings (Detzen and Loehlein, 2018;Evans, 2018b;Kamla and Komori, 2018;Locke et al, 2018;Marini et al, 2018). Several papers also draw attention to the opportunities relating to the agency, power (or lack of power), standing and motives of the translator and the interests in and politics of decision making in translation (see, especially, Ejiogu and Ejiogu, 2018;Evans, 2018b;Kamla and Komori, 2018;Nobes and Stadler, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The contributions to this AAAJ special issue also demonstrated that there is much still to be done for us as a community to begin to comprehend and address the impact of language and translation on our innovative and (hopefully) more inclusive knowledge creation endeavors. Thus, there is a considerable scope for the exploration of the power implications of language skills, and of the use of ELF, in diverse settings (Detzen and Loehlein, 2018;Evans, 2018b;Kamla and Komori, 2018;Locke et al, 2018;Marini et al, 2018). Several papers also draw attention to the opportunities relating to the agency, power (or lack of power), standing and motives of the translator and the interests in and politics of decision making in translation (see, especially, Ejiogu and Ejiogu, 2018;Evans, 2018b;Kamla and Komori, 2018;Nobes and Stadler, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of and opportunities inherent in drawing on linguistic theories, and collaboration with scholars in language sciences, are emphasized by Locke et al (2018), Hayoun (2018), and Bassnett et al (2018), while Evans (2018b) points out that, for example, the cultural turn in translation studies is highly relevant to accounting, and that there is considerable scope also to learn from and collaborate with scholars in international business/management, and organization studies, where considerable advances have been made in language and translation research. Evans (2018b) also suggests that researchers may further extend the use of commonly applied approachessuch as hermeneutics, constructivism, game theory and deconstructionto language translation in accounting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While grappling with the impacts of the pandemic, the accounting and finance area has been confronted with numerous other challenges, such as those related to longer term threats like climate change and the integration of TCFD (Task Force on Climate‐related Financial Disclosures) reporting (e.g., O'Dwyer and Unerman, 2020). Other issues with direct impact for the discipline include the increasing use of cloud accounting software, shifts to remote working and the greater use of AI, blockchain applications and digital technologies (such as automated data extraction and processing and fraud detection) (see also Cai, forthcoming; Locke et al ., 2018, Troshani et al ., 2019), alongside additional challenges around data security and control (e.g., Haapamäki and Sihvonen, 2019).…”
mentioning
confidence: 99%